2005
DOI: 10.1080/01431160512331316441
|View full text |Cite
|
Sign up to set email alerts
|

Low grazing angle radar imaging experiments over the South Falls sandbank

Abstract: A number of X-band radar data collection exercises have been conducted in the area of the South Falls sandbank, which were supported by two deployments with a research vessel that directly measured the tidal flow and water depth. Results from a total of 12 low grazing angle airborne radar data collections are presented. Nine sorties were flown with the Enhanced Surveillance Radar, using a synthetic aperture radar (SAR) mode. The other three aircraft sorties were flown using a real aperture scanning radar mode.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The details of this method are described chapter 3 of reference [10] and other references contained therein. The effects of current variations are often clearly evident on radar imagery from remote sensing satellites to low grazing angle airborne radar [12].…”
Section: Variation Of Tidal Currentsmentioning
confidence: 99%
“…The details of this method are described chapter 3 of reference [10] and other references contained therein. The effects of current variations are often clearly evident on radar imagery from remote sensing satellites to low grazing angle airborne radar [12].…”
Section: Variation Of Tidal Currentsmentioning
confidence: 99%
“…Signatures of normalized radar cross section (NRCS) modulation at the ocean surface due to sea bottom topography are visible on a variety of radar images derived by shore‐ and ship‐based radar as well as by real aperture radar (RAR) and synthetic aperture radar (SAR) on board airborne and spaceborne platforms [ McLeish et al , 1981; Hennings et al , 1994; Vogelzang et al , 1997; Lamont‐Smith et al , 2005]. A first descriptive explanation of such phenomena was given by De Loor [1981] and coworkers in the Netherlands.…”
Section: Introductionmentioning
confidence: 99%
“…The strain rate is a quantity of interest because it is well known to have an effect on the RCS of the sea surface (Alpers and Hennings 1984). Lamont-Smith et al (2005) have recently shown that surface strain rate can have a particularly strong effect on radar backscatter at low grazing angles and at low wind speeds. There are quantitative differences in the image produced in figure 7, depending on exactly how the current and the current gradient are calculated.…”
mentioning
confidence: 99%